GAME CHANGER – DEFINITION AND CLASSIFICATION: A HUMAN AND CHATGPT VIEW - Pierścieniak, Agata; Sopińska, Agnieszka; Pierścieniak, Grzegorz (Organizacja i Kierowanie, 2023)
The world in which organizations operate is changing, and researchers are increasingly trying to determine not only the effects or adaptability to change but also to identify its causes. To better understand what changes our reality, we have developed the definitions and main features of a game changer to describe and characterize it. We used different methods in our research, using a grounded theory strategy combining analyses in a human-computer model. This combination involved both thematic modeling with different level of systematicity and systematic manual coding of manuscripts. As a novelty, we introduced ChatGPT, which enabled deepening our syntheses, complementing and generalizing the results. Defining what is and what is not a game changer will enable better recognition of the causes of change, which is the starting point not only in decision-making, but also in the concept of organizational adaptation or change management theory.